School Readiness and Achievement Motivation as Academic Achievement Predictors in Elementary School Students - Mariyat, Lely I.; Affandi, Ghozali R.; Afandi, Rifki (International Journal of Psychosocial Rehabilitation, 2020)
Academic achievement is one of the main indicators of student success in school, but in this condition not all students obtain satisfactory academic results. Theoretically there are several factors that influence the achievement of high learning achievement, especially in early elementary students, that is school readiness and motivation to learn. The purpose of this research is to determine the role and predictive power of school readiness and also achievement motivation for academic achievement of first grade Elementary School students. The research method used in this research is quantitative correlation with a survey model. The variables in this research consist of 3 variables, they are school readiness, achievement motivation and academic achievement. School readiness is measured by the Nijmeegse Schoolbekwaamheids Test (NST), achievement motivation is measured by a scale of achievement motivation and academic achievement is measured using the report cards on student learning outcomes at school. The sample in this research is 75 students from 80 first grade students in Sidoarjo. Analysis of the data used is multiple regression analysis. The results of the research have a simultaneous influence on the variable readiness to enter elementary school and achievement motivation on academic achievement by getting the value of F = 18.866 (sig 0.000 <0.05). The influence of these two variables (School Readiness and Achievement Motivation) on Academic Achievement is 0.326 (32.6%). While 67.4% is influenced by other variables. The urgency of this research will be useful for parents and teachers at the Kindergarten and Elementary School level, especially first grade regarding the ef orts made by parents and teachers to improve student learning achievement while at the Elementary School level.